1979
DOI: 10.1097/00000658-197905000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Biliary Surgery in Acute Pancreatitis

Abstract: The timing of biliary surgery remains controversial in patients with acute pancreatitis associated with cholelithiasis. Eighty hospital admissions for acute pancreatitis, occurring in 74 patients with cholelithiasis, have therefore been reviewed. Among 22 patients who underwent abdominal surgery during the first week of treatment, there were five deaths (23%) and four patients (18%) who required more than seven days of intensive care. Fifty-eight episodes of pancreatitis were managed nonoperatively during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0
21

Year Published

1980
1980
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(157 citation statements)
references
References 17 publications
1
135
0
21
Order By: Relevance
“…The evidence that does exist originates mainly from older retrospective studies that observed no recurrent ABP after a cholecystectomy compared with a 25% to 61% rate of ABP recurrence with conservative management [11][12][13][14][15][16][17]. From a retrospective population-based cohort study, it was concluded that a cholecystectomy reduces the risk of a recurrent or de novo ABP almost to the same level as found in the general population [18].…”
Section: Cholecystectomy Versus Conservative Treatmentmentioning
confidence: 99%
“…The evidence that does exist originates mainly from older retrospective studies that observed no recurrent ABP after a cholecystectomy compared with a 25% to 61% rate of ABP recurrence with conservative management [11][12][13][14][15][16][17]. From a retrospective population-based cohort study, it was concluded that a cholecystectomy reduces the risk of a recurrent or de novo ABP almost to the same level as found in the general population [18].…”
Section: Cholecystectomy Versus Conservative Treatmentmentioning
confidence: 99%
“…Mohan et al while evaluating the relative roles of MRCP and EUS in investigating CBD calculi "evidence based practice" methods concluded MRCP should be the first line of investigation of CBD calculi [19]. The frequency and morbidity of recurrent pancreatitis are great, as undiagnosed biliary disease carries a recurrence rate of 20-50%, whereas the risk of recurrent pancreatitis associated with biliary stones decreases to less than 5% after corrective surgery [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies done to date have demonstrated a risk of recurrent biliary pancreatitis from 25 to 63% when cholecystectomy was delayed until after discharge from the index hospitalization. 30,31,32 In a retrospective observational study of 281 patients with ABP, Ito et al demonstrated gallstone-related complications in 33% of patients who did not have index cholecystectomy, with recurrent ABP found in 13.4% of patients (versus no recurrences in the index cholecystectomy group). Of note, almost one third of recurrences occurred within 2 weeks after discharge, and half of recurrences occurred within 4 weeks.33 They also looked at ERCP with ES as definitive treatment in 42 out of the 119 patients who did not have index cholecystectomy.…”
Section: Managementmentioning
confidence: 99%